PHYSIOLOGICAL RESPONSE OF BROILER CHICKENS TO ACETYLSALICYLIC ACID (ASA) SUPPLEMENTATION IN DRINKING WATER - E.R., Ameh; A.A. , Okpe; O.A., Ejiwoye (Kashere Journal of Animal Science, 2025)
This study evaluated the effects of Acetylsalicylic Acid (ASA) supplementation in drinking water on the growth performance and physiological responses of broiler chickens raised under tropical conditions. A total of 144 two-week-old broilers were randomly assigned to four treatments (0.00, 1.00, 1.50, and 2.00 g ASA/L of water) in a completely randomized design. Birds were monitored over six weeks for growth parameters (weight gain, feed intake, feed conversion ratio) and physiological indices (cloacal temperature, respiratory rate, and pulse rate). Results revealed that while initial weight and feed intake were not significantly affected (p>0.05), ASA supplementation significantly (p<0.05) improved final weight, daily weight gain, and feed conversion ratio, with the highest performance observed at 2.00 g/L. Physiological responses also improved with increasing ASA levels, as evidenced by reduced cloacal temperature, respiratory rate, and pulse rate, suggesting better thermal regulation and reduced metabolic stress. These findings indicate that ASA supplementation, particularly at 2.00 g/L, enhances broiler performance and welfare under heat stress, making it a viable management strategy in tropical poultry production.